Antioxidant activity of some natural essential oils in Vietnam: Comparison between QSAR simulation and experimental study - My, Tran Thi Ai; Hieu, Le Trung; Hai, Nguyen Thi Thanh; Phuong, Ton Nu My; Loan, Huynh Thi Phuong; Thuy, Bui Thi Phuong; Nhung, Nguyen Thi Ai (Hue University Journal of Science: Natural Science, 2020)
The antioxidant activity of essential oils from leaves of Piper betle L. (T) and Cleistocalyx operculatus L. (V) and aerial parts of Ageratum conyzoides L. (H), indigenously grown in Thua Thien Hue province, Vietnam, is investigated. The quantitative structure–activity relationship (QSAR) model comprising 4-hydroxy-chromene-2H-one and its 26 derivatives is used to predict the radical scavenging activity of T, V, and H. The radical scavenging activity of the oils is experimentally determined with DPPH (1,1-diphenyl-2-picrylhydrazyl) via IC50 values. The experimental IC50 values are in good agreement with those obtained from the QSAR model. The IC50 value of Piper betle L. is 3.71 mg/mL, comparable to that of the strong antioxidant ascorbic acid (3.03 mg /mL).